A Computational Bibliometric Analysis of Esport Management using VOSviewer - Ginting, Selvia Lorena Br (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
The project aims to combine visualization study with VOSviewer and Publish or Perish software to conduct a computerized bibliometric analysis of the phrase "Esports Management." The method used descriptive-quantitative approach in conjunction with bibliometric analysis. The data was obtained from the Google Scholar search results for "Esports Management." There were 999 articles published between 2017 and 2021, with an increase each year except for 2021 to 2022. This may be demonstrated in 2017 with 58 articles, in 2018 with 92 pieces, in 2019 with 160 articles, in 2020 with 242 articles, and in 2021 with a huge rise to 335 articles. In 2022, however, the number of articles had significantly decreased to 64. Based on further findings of this research, it can be concluded that there are several understudied sectors in Esports Management that may be examined further to increase the efficacy of Management in Esports. It is anticipated that this research will also serve as an example for further studies in defining and evaluating the research subject, as well as for the Esports participants' management team.